2016
DOI: 10.1186/s40665-016-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of mineral soil carbon decomposition in shrub and graminoid tundra, west Greenland

Abstract: Background: Shrub expansion is transforming Arctic tundra landscapes, but the impact on the large pool of carbon stored in high-latitude soils is poorly understood. Soil carbon decomposition is a potentially important source of greenhouse gases, which could create a positive feedback to atmospheric temperature. Decomposition is temperature sensitive, but the response to temperature can be altered by environmental variables. We focus on mineral soils, which can comprise a substantial part of the near-surface ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…With C addition, CO 2 emission rate increased dramatically and showed a pulse response, whereas a monotonic declining pattern was observed for all soils without C addition (Figures 1 and 3). This supports the idea that the microorganisms in the soils collected from the field might have limited access to readily available C. The pulse response pattern is common in response to C substrate addition (Cleveland et al, 2002;Kuzyakov, 2010;Tian et al, 2014), although some incubation studies report a decline of CO 2 emission rates due to rapid metabolism of the labile C substrate (e.g., Bradley-Cook, Petrenko, Friedland, & Viginia, 2016;Jing et al, 2017;Tian et al, 2014;Zhou, Hui, & Shen, 2014). Increasing emissions with C addition could indicate the growth of the microbial population, decomposition of the added labile substrate and/or increasing microbial activity through the priming (Blagodatskaya & Kuzyakov, 2008;Blagodatsky et al 2010;Mehnaz et al 2019).…”
Section: Discussionsupporting
confidence: 62%
“…With C addition, CO 2 emission rate increased dramatically and showed a pulse response, whereas a monotonic declining pattern was observed for all soils without C addition (Figures 1 and 3). This supports the idea that the microorganisms in the soils collected from the field might have limited access to readily available C. The pulse response pattern is common in response to C substrate addition (Cleveland et al, 2002;Kuzyakov, 2010;Tian et al, 2014), although some incubation studies report a decline of CO 2 emission rates due to rapid metabolism of the labile C substrate (e.g., Bradley-Cook, Petrenko, Friedland, & Viginia, 2016;Jing et al, 2017;Tian et al, 2014;Zhou, Hui, & Shen, 2014). Increasing emissions with C addition could indicate the growth of the microbial population, decomposition of the added labile substrate and/or increasing microbial activity through the priming (Blagodatskaya & Kuzyakov, 2008;Blagodatsky et al 2010;Mehnaz et al 2019).…”
Section: Discussionsupporting
confidence: 62%
“…Understory vegetation participates in the nutrient cycling of soil C and N process through several different ways. The graminoid vegetation has a fibrous root system, with higher decomposition rates compared with the rhizomes of Dicranopteris , which would potentially increase soil organic matter inputs [ 40 , 41 ]. Additionally, due to differences in functional traits, understory vegetation types might alter litter decomposition rates and microbial activities by affecting soil moisture, temperature, and other environmental factors [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al (2011) reported higher C pools under graminoid than shrub vegetation for both organic and mineral soil. Furthermore, Bradley-Cook et al (2016) found that microbial respiration in graminoid mineral soils is more sensitive to increases in temperature than shrub mineral soils, suggesting vulnerability of the graminoid soil C pool to changes in climate. This study contributes an original data set on mineral soil C and N pools in two dominant Arctic tundra vegetation types and provides baseline data to which future shifts in vegetation and changes in C and N pools can be compared.…”
Section: Introductionmentioning
confidence: 98%